Pedagogical Bases of Formation of Key Information Technology Competencies Polytechnic Institute Graduates - Ushatikova, Irina I.; Rakhmanova, Alsu R.; Kireev, Vasiliy S.; Chernykh, Anatoly O.; Ivanov, Mikhail A. (International Journal of Economics and Financial Issues, 2016)
The article based on the analysis of the literature and experience in the field of economic education is considered a system of key concepts on the topic, as well as features of the introduction of competence approach in teaching practice Polytechnic Institute, the problem of realization competence approach in higher education, the formation of key information technology competencies, ensuring high availability Polytechnic Institute graduates to solve problems in the practice of the specialty, modern requirements to the society and the state system of vocational education at all levels, the task of creating these pedagogical conditions, which would help improve the quality of training of future specialists. This article lists didactic, psycho-pedagogical, organizational and pedagogical conditions that are necessary to improve the level of information technology training of future specialists. Their implementation will create the necessary information technology economist competence. Keywords: economic reforms, economic education, polytechnic education, competence, professionalism JEL Classifications: A10, A29, Q15